The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.20965/jaciii.2017.p0371
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Communication Aid App with iOS Devices to Support Children/Persons with Speech Disabilities Improvement in Obtaining Positioning Information with iBeacon as Near Field Radio Communication Technology

Abstract: Communication has such a vital function as the foundation of human social life that speech disabilities can drastically deteriorate people’s quality of life. The author has developed a voice output communication aid (VOCA) to enable children/persons with speech disabilities to communicate with other people according to conversation situations with iOS devices with global positioning system (GPS), positional information acquiring technology (iBeacon), and a clock function installed. The developed technology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Among the location and environment data-sensing technologies that were used, the app had relatively the lowest performance in detecting and transmitting iBeacon data. Although relatively higher, a previous study on the use of the iBeacon system in Friendly VOCA showed the same result [7]. This trend emphasizes the possible problem with the placement of iBeacon devices and not the mobile apps developed.…”
Section: App Server/api Performancesupporting
confidence: 54%
See 4 more Smart Citations
“…Among the location and environment data-sensing technologies that were used, the app had relatively the lowest performance in detecting and transmitting iBeacon data. Although relatively higher, a previous study on the use of the iBeacon system in Friendly VOCA showed the same result [7]. This trend emphasizes the possible problem with the placement of iBeacon devices and not the mobile apps developed.…”
Section: App Server/api Performancesupporting
confidence: 54%
“…In 2017, Karita [7] developed Friendly VOCA, a user-friendly VOCA iOS mobile app that enables children and individuals with speech and/or intellectual disabilities to communicate with other people independently. Unlike other available VOCAs, Friendly VOCA has the ability to automatically switch displays or interfaces that match the user's location at a specific time [7]. To achieve this, Friendly VOCA uses GPS technology to identify the user's current outdoor location in terms of map coordinates (latitude and longitude).…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations